USING DIGITAL TOOLS IN TEACHING A FOREIGN LANGUAGE (Ta'limning zamonaviy transformatsiyasi, 2024)
At present, the educational process requires not only traditional approaches to learning, but also unique methods of teaching students. The age of technology allows professors come up with great ideas using digital tools, especially when teaching foreign languages.